Accessing Yahweh’s presence: Ethical implications of the entrance liturgy of Psalm 15 - Boloje, Blessing Onoriode; Groenewald, Alphonso (Stellenbosch Theological Journal, 2016)
This article is an examination of the theological foundation that lies at the core of the expression of Israelite piety; that is, the foundational and defining characteristic reflexes in Israelite religious experience of human access to Yahweh. The article is rightfully anchored on the premise that individuals and communities have the privilege of access to Yahweh. However, Psalm 15 presents certain ethical preconditions of continuous experience of access and intimacy with Yahweh. These ethical preconditions constitute Israel’s practice of pilgrimage with Yahweh, a practice that witness to the passionately penetrating symbolism of the requirements of a consistency of life direction. Psalm 15 insists that those who approach Yahweh for divine help or worship may do so having their internal and external condition in harmony with Yahweh. They must do so from hearts and lives of integrity. This article thus focuses on the context, content and concludes by reflecting on the ethical implications of Psalm 15 for both individual and corporate experience of worship.